5S Ribosomal DNA of Genus Solanum: Molecular Organization, Evolution, and Taxonomy - Tynkevich, Yurij O.; Shelyfist, Antonina Y.; Kozub, Liudmyla V.; Hemleben, Vera; Panchuk, Irina I.; Volkov, Roman A. (Frontiers in Plant Science, 2022)
The Solanum genus, being one of the largest among high plants, is distributed worldwide and comprises about 1,200 species. The genus includes numerous agronomically important species such as Solanum tuberosum (potato), Solanum lycopersicum (tomato), and Solanum melongena (eggplant) as well as medical and ornamental plants. The huge Solanum genus is a convenient model for research in the field of molecular evolution and structural and functional genomics. Clear knowledge of evolutionary relationships in the Solanum genus is required to increase the effectiveness of breeding programs, but the phylogeny of the genus is still not fully understood. The rapidly evolving intergenic spacer region (IGS) of 5S rDNA has been successfully used for inferring interspecific relationships in several groups of angiosperms. Here, combining cloning and sequencing with bioinformatic analysis of genomic data available in the SRA database, we evaluate the molecular organization and diversity of IGS for 184 accessions, representing 137 species of the Solanum genus. It was found that the main mechanisms of IGS molecular evolution was step-wise accumulation of single base substitution or short indels, and that long indels and multiple base substitutions, which arose repeatedly during evolution, were mostly not conserved and eliminated. The reason for this negative selection seems to be association between indels/multiple base substitutions and pseudogenization of 5S rDNA. Comparison of IGS sequences allowed us to reconstruct the phylogeny of the Solanum genus. The obtained dendrograms are mainly congruent with published data: same major and minor clades were found. However, relationships between these clades and position of some species (S. cochoae, S. clivorum, S. macrocarpon, and S. spirale) were different from those of previous results and require further clarification. Our results show that 5S IGS represents a convenient molecular marker for phylogenetic studies on the Solanum genus. In particular, the simultaneous presence of several structural variants of rDNA in the genome enables the detection of reticular evolution, especially in the largest and economically most important sect. Petota. The origin of several polyploid species should be reconsidered.